DETEKSI GEJALA ERUPSI STROMBOLIAN GUNUNGAPI RAUNG JAWA TIMUR MENGGUNAKAN NORMALIZED THERMAL INDEX DARI DATA MODIS - Suwarsono, Suwarsono; Hidayat, Hidayat; Suprapto, Totok; Yulianto, Fajar; Sari, Nurwita Mustika; Parwati, Parwati; Asriningrum, Wikanti (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2015)
Geologically, most of Indonesia is located on subduction zone of the Pacific ring of fire that causes many emerging active volcanoes. The existence of active volcanoes has an implications that the volcanic eruption could occur at any time. This study aims to detect the precursors of volcanic eruption by using parameters NTI (Normalized Thermal Index) derived from MODIS data. Volcanic object selected is Raung Volcano in East Java, where around June to July 2015 showed an increase in volcanic activity and was erupted. Data processing method includes processing of Landsat-8 for the determination of the area of interest (caldera and active crater), MODIS image processing for NTI measurement, and analysis of spatial and temporal patterns of NTI. The results showed that the precursors of a volcanic eruption can be detected from the increasing of the NTI value in the kaldera and its value which relatively higher than in the surrounding area. NTI parameters have proven to have a good ability to distinguish between the kaldera and other objects during eruption period. In case of Raung Volcano, NTI value = 0.06 can be applied as a threshold value for the eruption of this volcano.